PENINGKATAN PRODUKTIVITAS KOPERASI SERBA USAHA ”SUBAK KEDUA”MELALUI PENERAPAN MOBIL SLEP “3 IN 1” - Budiana D; A. Subagia; A. Suryawan; G. Karohika (Buletin Udayana Mengabdi, 2010)
ABSTRAC Peguyangan Kangin village has rice land about 77.65% of the total area of the village, and 37.33% of the population in the village has a daily job as farmers and laborers of farms.Most of the farmers and rural laborers in Peguyangan Kangin has joined 3 subak organisations. One of the Subaks is the second subak Peguyangan Kangin having Koperasi Serba Usaha. Types of the cooperation operation are such as savings and loan units, units of livestock, fisheri existes units, and units of service. Based on profile data Peguyangan Kangin village in 2008, control of economic assets was handled by the public in the form of assets and agricultural machinery industry . There are only 2 engines and 3 rice mills tractor operates in this village, and they belong to personal property ownership status. if the ratio is calculated using the average means the rice milling machine 1 serving approximately 151.9 hectares of rice fields. It means facilities of agricultural machinery is still unadequate and the distance from the fields to place far enough away so that the mill needs transport that eventually lead to the transportation costs burdening farmers. Through the program ‘vucer team’ that has been successfully designing and building cars slep 3 in 1 whereas the car is equipped with a diesel engine dafa 24 pk brand that serves to move the 3 engines at once; slep machines, polishing machines, and machine rice thresher. From the results of experiments or demonstrations using cars slep 3 in 1 is obtained very satisfactory results, which in this 1-hour car can get as much slep dried grain with 125 kg of very clean rice yields.